Gambling Behavior and Risk Factors in Preadolescent Students: A Cross Sectional Study - Vegni, Nicoletta; Melchiori, Francesco Maria; D’Ardia, Caterina; Prestano, Claudia; Canu, Massimo; Piergiovanni, Giulia; Di Filippo, Gloria (Frontiers in Psychology, 2019)
Although gambling was initially characterized as a specific phenomenon of adulthood, the progressive lowering of the age of onset, combined with earlier and increased access to the game, led researchers to study the younger population as well. According to the literature, those who develop a gambling addiction in adulthood begin to play significatively before those who play without developing a real disorder. In this perspective, the main hypothesis of the study was that the provide in order to make a first description of the phenomenon of gambling behavior in this younger population is already associated to specific characteristics, that could led to identify risk factors. In this paper are reported the results of an exploratory survey on an Italian sample of 2734 preadolescents, aged between 11 and 14 years, who replied to a self-report structured questionnaire developed ad hoc. Firstly, data analysis highlighted an association between the gambling behavior and individual or ecological factors, as well as a statistically significant difference in the perception of gambling between preadolescent who play game of chance and the others. Similarly, the binomial logistic regression performed to ascertain the effects of seven key variables on the likelihood that participants gambled with money showed a statistically significant effect for six of them. The relevant findings of this first study address a literature gap and suggest the need to investigate the preadolescent as a cohort in which identify predictive factors of gambling behavior in order to design effective and structured preventive interventions.